Simultaneous effect of mechanical tension on electrical lifetime of some inorganic composites - Ozcanli, Y. Lenger; Boydag, F. S.; Alekberov, V. A.; Hikmet, I.; Canturk, M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In this work, the simultaneous effect of mechanical tension (sigma) and electrical strength (E) on electrical lifetime (TE) for pure low density polyethylene (LDPE)/polypropylene (PP) and composites with different commercial diamond-additive/glass fiber additive percentages is experimentally studied. The role of this effect on degradation mechanisms is investigated. log TE,sigma - f(E) and E sigma - f(sigma) graphs are drawn, new equations are proposed and determined parameters at constant temperature for pure LDPE and PP, and for optimum composites (LDPE/0.5% diamond, PP/0.5% glass fiber) are listed. The results indicate that the degradation speed decreases more for composites than for pure LDPE and PP. The electrical durability for composites after the simultaneous effect of (T decreases 18-20%, while for pure LDPE and PP, it decreases 50-55%.
Keywords: inorganic composites; electrical properties; activation energy; degradation speed; POLYMER COMPOSITES; POLYPROPYLENE; POLYETHYLENE; BLENDS; Physics